Malassezia-Can it be ignored? - Ambujavalli Balakrishnan Thayikkannu; Anupma Jyoti Kindo; Mahalakshmi Veeraraghavan (Wolters Kluwer Medknow Publications, 2015)
Genus Malassezia comprises of 14 species of "yeast like fungi," 13 of which are lipophilic and 1 is nonlipophilic. They are known commensals and in predisposed individuals they commonly cause a spectrum of chronic recurrent infections. They rarely also cause serious illnesses like catheter-related blood stream infections, CAPD associated peritonitis etc., Though these fungi have been known to man for over 150 years, their fastidious nature and cumbersome culture and speciation techniques have restricted research. Since the last taxonomic revision, seven new species have been added to this genus. Their ability to evade the host immune system and virulence has increased the spectrum of the diseases caused by them. These agents have been implicated as causal agents in common diseases like atopic dermatitis recently. Though culture-based research is difficult, the new molecular analysis techniques and facilities have increased research in this field such that we can devote more attention to this genus to study in detail, their characteristics and their growing implications implications in the clinical scenario.